Insight into Posterior Urethral Valve from Our Experience: Paradigm Appended to Abate Renal Failure - Chatterjee, Uday Sankar (J Indian Assoc Pediatr Surg, 2020)
OBJECTIVE: The objective of the study was to share our experience of management of posterior urethral valve (PUV) and to suggest a paradigm to impede upstaging of chronic kidney disease (CKD) and prevent end-stage renal failure (ESRF). PATIENTS AND METHODS: We have treated 332 patient of PUV from March 2005 to April 2016, Of which 272 case records had adequate data to be analyzed. The mean age was 2.48 years (range: 1 day–18 years). We did primary fulguration in 231 patients, of which five patients needed bilateral ureterostomy for obstinate high creatinine level. The remaining 36 patients had primary fulguration done elsewhere. RESULTS: The mean duration of follow-up was 7.8 years (range 3–14 years). In the end of this study, 10 patients had down staging in CKD, 36 patients had up staging in CKD, and 9 patients ended in ESRF (3.8%). CONCLUSIONS: Detection of deterioration of renal function with creatinine clearance along with identifying the causes of deterioration and necessary interventions would help to arrest upstaging of CKD otherwise that might end in ESRF. From this study and reviewing the literature, we presume that the rhabdosphincter spasm underneath actually renders bladder outlet obstruction, and cusps of PUV, particularly in neonates, amplify the obstruction, following that bladder outlet obstruction cascades detrusor hypertrophy, bladder neck hypertrophy/obstructions, and ureterovesical junction obstruction/reflux, causing gradual damage to the bladder and upper tract and deterioration of renal function as a consequence.